Motivation, Empowerment, and Innovation: Teachers' Beliefs About How Participating in the Edmodo Math Subject Community Shapes Teaching and Learning - Trust, Torrey (Journal of research on technology in education, 2017)
Educators around the world participate in virtual communities, social media sites, and online networks in order to gain support and ideas for improving their practice. Many researchers have explored how and why teachers participate in these online spaces; however, there is limited research on how participation might impact teaching and learning. This study was designed to examine how K-12 teachers' participation in the Edmodo math subject community, an informal online space for educators, shaped their learning and practice. Data were collected through an online survey of 150 participants and in-depth, follow-up interviews with 10 participants. Three themes emerged from the participants' responses: motivation, empowerment, and innovation. The participants were motivated to spend time learning how to improve their practice, they felt empowered to make changes to their practice, and they believed they were able to adopt innovative, student-centered practices. Implications and ideas for further research are discussed.